PRESENTATION OF PSYCHOLOGICAL DISTRESS IN PSYCHIATRIC CLIENTELE IN TERTIARY CARE UNITS (The Research of Medical Science Review, 2025)
Literature underscores the significance of addressing psychological distress in psychiatric patients in a holistic and compassionate manner as this can have a profound impact on their quality of life by influencing their overall wellbeing. The present research followed a descriptive cross sectional research design and attempted to identify the role of psychological distress on mental health and general wellbeing of psychiatric clients presented in tertiary care setups. For this purpose, 200 individuals attending tertiary care psychiatric treatment facilities were selected through purposive sampling technique. All participants were diagnosed with a clinically significant psychological disorder and were between the age of 18 and 65 years. The educational level ranged from illiteracy to post graduation. Significant variations in presentation of rates of different dimensions of psychological distress was observed. Gender was found to be a leading element behind variations in the presentation of different dimensions of psychological distress in the present sample. The findings were discussed in the light of research studies conducted in Pakistan and abroad.